Hyperbilirubinemia in the newborn infants; unbound bilirubin approach - Achmad Surjono, Achmad Surjono (Universitas Gadjah Mada, 1995)
A guideline for management of hyperbilirubinemia in the newborns based solely on total/indirect serum bilirubin levels is considered outmoded. An approach to the identification of newborns at risk of bilirubin toxicity due to the increase of unbound bilirubin is proposed. Unbound bilirubin can easily enter the brain and bind to the nerve cells.A peroxidase oxidation method using unbound bilirubin - analyzer (UB-analyzer) offers a rapid, accurate and reproducible measurement of unbound bilirubin. Phototherapy, either continuous or intermittent can be applied to term and preterm infants on the monitoring of unbound bilirubin levels.Temporary cessation of breast-feeding is not advised in healthy term newborns with hyperbilirubinemia. On the contrary, more frequent feeding is advocated. Caution and substitution should be taken in giving any drugs having a potent displacer on bilirubin-albumin binding, especially In premature infants.Key words : newborn infants –hyperbilirubinemia – unbound bilirubin – phototherapy – displacing drugs